SISR of Hyperspectral Remote Sensing Imagery Using 3D Encoder-Decoder RUNet Architecture - Aburaed, Nour; Alkhatib, Mohammed Q.; Marshall, Stephen; Zabalza, Jaime; Ahmad, Hussain Al (IEEE International Geoscience and Remote Sensing Symposium proceedings, 2022)
Single Image Super Resolution (SISR) refers to the spatial enhancement of an image from a single Low Resolution (LR) observation. This topic is of particular interest to remote sensing community, especially in the area of Hyperspectral Imagery (HSI) due to their high spectral resolution but limited spatial resolution. Enhancing the spatial resolution of HSI is a pre-requisite that boosts the accuracy of other image processing tasks, such as object detection and classification. This paper deals with SISR of HSI through the 3D expansion of Robust UNet (RUNet). The network is developed, trained, and tested over two datasets, and compared against the original 2D-RUNet and other state-of-the-art approaches. Quantitative and qualitative evaluation show the superiority of 3D-RUNet and its ability to preserve the spectral fidelity of the enhanced HSI.